Pinecone 1954 - Valdosta State College (Valdosta State College, 1954)
How had four years passed so quickly? "Why, only yesterday we were Freshmen." At the beginning of the year, we Seniors were busy with the Halloween Carnival, Junior-Senior Frolics, informal dances, then the last Hanging of the Greens, in the Rotunda of Ashley Hall. Then came May-Day, the Queen and her Court, and we felt as if four wonderful years at V.S.C. were fun, if a little sad. Caps and gowns—graduation—no, there wouldn't be time to reminisce about it all, but there would be time afterward and for years to come.
A year book was published for Valdosta State College from 1925-1977, under the name The Pinecone. From 1981-1987, a yearbook was published called Milestones. Valdosta State University had three names during this period, Georgia State Womans College, 1925-1950; Valdosta State College, 1950-1993; and Valdosta State University 1993-present.
Keywords: yearbook; Americana